An Escherichia Coli Epizootic in Captive Mallards (Anas platyrhynchos) - Miller, Debra L.; Hatkin, Josh; Radi, Zaher A.; Mauel, Michael J. (International Journal of Poultry Science, 2004)
Captive mallard (Anas platyrhynchos) facilities are a common source of birds for game preserves. An outbreak of Escherichia coli septicemia in 2 and 8-wk-old ducklings was diagnosed in a captive mallard facility in South Georgia. Additionally, fungal hyphae were observed in the 2-wk-old birds but not the 8-wk-old birds. Ducklings were overcrowded in both the brooding facility (2-wk-old birds) and within the flight enclosures. The single small pond within the flight enclosure was contaminated with E. coli. Although the stress of captivity may have contributed to the ducklings` deaths, poor husbandry was the primary factor in these birds` deaths.